Causal associations between modifiable risk factors and isolated REM sleep behavior disorder: a mendelian randomization study - Zhang, Ru-Yu; Li, Fu-Jia; Zhang, Qian; Xin, Li-Hong; Huang, Jing-Ying; Zhao, Jie (Frontiers in Neurology, 2024)
Objectives: This Mendelian randomization (MR) study identified modifiable risk factors for isolated rapid eye movement sleep behavior disorder (iRBD).Methods: Genome-wide association study (GWAS) datasets for 29 modifiable risk factors for iRBD in discovery and replication stages were used. GWAS data for iRBD cases were obtained from the International RBD Study Group. The inverse variance weighted (IVW) method was primarily employed to explore causality, with supplementary analyses used to verify the robustness of IVW findings. Co-localization analysis further substantiated causal associations identified via MR. Genetic correlations between mental illness and iRBD were identified using trait covariance, linkage disequilibrium score regression, and co-localization analyses.Results: Our study revealed causal associations between sun exposure-related factors and iRBD. Utilizing sun protection (odds ratio [OR] = 0.31 [0.14, 0.69], p = 0.004), ease of sunburn (OR = 0.70 [0.57, 0.87], p = 0.001), childhood sunburn occasions (OR = 0.58 [0.39, 0.87], p = 0.008), and phototoxic dermatitis (OR = 0.78 [0.66, 0.92], p = 0.003) decreased iRBD risk. Conversely, a deep skin color increased risk (OR = 1.42 [1.04, 1.93], p = 0.026). Smoking, alcohol consumption, low education levels, and mental illness were not risk factors for iRBD. Anxiety disorders and iRBD were genetically correlated.Conclusions: Our study does not corroborate previous findings that identified smoking, alcohol use, low education, and mental illness as risk factors for iRBD. Moreover, we found that excessive sun exposure elevates iRBD risk. These findings offer new insights for screening high-risk populations and devising preventive measures.